(E)-N′-(3-Fluorobenzylidene)-4-methylbenzohydrazide - Hua-Nan Hu (Acta Crystallographica Section E, 2012)
In the title compound, C15H13FN2O, the dihedral angle between the benzene rings is 16.9 (2)°. The F atom and the O atom are in a syn conformation. In the crystal, molecules are linked by N—H...O hydrogen bonds to generate C(4) chains propagating along the b-axis direction.